Customer satisfaction towards Amanah Saham Nasional Berhad (ASNB) agents service level in Kuala Lumpur / Nani Ajit - Ajit, Nani (Faculty of Business and Management, 2006)
Customer satisfaction is increasingly becoming more important as more companies strive for quality in their products and services. Hence, if the company's perceived performance exceeds a customer's expectations (a positive disconfirmation), then the customer feels satisfied. On the other hand, if the company's perceived performance falls short of a customer's expectation (a negative disconfirmation), then the customer feels dissatisfied. ASNB have identified five levels of ASNB service agents and is measuring of ASNB own service counters, ASNB agents customer service counter and including agents knowledge and services, ASNB agents for unit trust fund information and ASNB agents environment facilities. To serve the purpose, an exploratory research is carried-out to obtain result about how customer's satisfaction based on the perceived expectation and actual satisfaction on ASNB agents' service level.